Innovation, advertising, personal selling, and sustainability in the industries massively benefited from major public health emergencies: paradoxical evidence from China - Xie, Guangying; Zhang, Cancan; Fang, Qianqian; Tang, Xiaole; Zhang, Yani (Frontiers in Public Health, 2023)
While major public health emergencies have severe socio-economic impacts, they may also present many opportunities for certain industries. For these industries that have benefited sig-nificantly, the traditional emphasis on improving business performance through increased in-vestment in innovation, marketing and sustainability may face contextual applicability challenges. By using the data of healthcare industry in China during Covid-19 and the methods of hierarchical regression, moderating effect test and robustness test, this paper finds that innovation, advertising, and environmental sustainability have significant negative impacts on profitability, while per-sonal selling, social sustainability, and governance sustainability have significant positive im-pacts on profitability in the industries massively benefited from major public health emergencies. Besides, social sustainability can significantly moderate the relationship between innovation and profitability. These findings challenge previous research in the relationship between innovation, marketing, sustainability and performance, and can be used to guide resource allocation decisions in the practice.